Sustainable building: Achieving thermal comfort in hot and humid climate using building performance simulation - Pratiwi, Niniek; Djafar, Abdi Gunawan; Rahmayanti, Rahmayanti; Mutmainnah, Nur; Kaharu, Arlan (Sustinere: Journal of Environment and Sustainability, 2025)
The scientific community has established a clear link between the built environment and various environmental problems. Various strategies have been implemented to mitigate the negative impacts of buildings and to address broader environmental challenges. One such strategy is the adoption of sustainable building practices. Among the factors contributing to the environmental impacts of buildings, efforts to achieve thermal comfort play significant role. Particularly due to the energy consumption involved. At the same time, thermal comfort is also a critical factor influencing human productivity, including academic performance. Comfortable learning environments are known to enhance students’ learning outcomes. This research presents a case analysis conducted at State Elementary School 91 Sipatana, Gorontalo City, Indonesia. Measurements were carried out on December 24, 2022, from 06.00 to 18.00. Room temperature was recorded using an Elitech GSP-6 data logger, and further simulations were carried out using Ladybugs and Honeybees. The purpose of this study is to evaluate building performance in achieving thermal comfort by considering solar radiation exposure, roof surface temperature, room temperature, and Predicted Mean Vote (PMV) values. Comparisons were made across different building materials, including variation in roofing, wall types, and ventilation systems. The wall in the existing structure are composed of concrete with a fiber wall. The findings highlight the impact of roofing materials, wall construction, and ventilation on the PMV, roof surface temperature, and indoor air temperature. Based on-site measurements, the average classroom temperature was 30.5°C. Among the simulation configurations, Model 3 which featured a metal roof with a cool roof technology, concrete walls, and added ventilation demonstrated the best thermal performance. It maintained a roof surface temperature just above 25°C and an indoor air temperature close to 30°C, showing the effectiveness of cool roof technology and adequate ventilation in reducing heat accumulation.